Development of learning media for the Google site web-based on character - Kardiana Metha Rozhana; Wahyu Widodo; Dwy Cahyono; Firsta Bagus Sugiharto; Chusnul Chotimah (University of Muhammadiyah Malang, 2023)
This research aims to develop learning media based on the Google site web-based on character values, which will help elementary school teachers and students learn, especially on social studies content on ethnic and cultural diversity material in Indonesia. This study uses the ADDIE R&D model with five stages. The results of the feasibility validation from design experts show a percentage of 88.5% with excellent and valid criteria. Material experts perform a presentation of 86.6% with excellent and valid criteria. Linguists with a presentation of 80% with excellent and valid criteria. While aspects of application and student attractiveness with a presentation of 85% and teachers with a presentation of 96%. From the aspect of effectiveness, with a presentation of 98.4%, and from the aspect of student PPK assessment, with a presentation of 94.2%. These results indicate that media can be applied to process learning in schools, especially in grade IV SD.